Spatial, demographic, and phylogenetic patterns of Bartonella diversity in bats - McKee, Clifton Dyer, author; Webb, Colleen T., advisor; Kosoy, Michael Y., committee member; Funk, W. Chris, committee member; Schountz, Tony, committee member; Hayman, David T. S., committee member (Colorado State University. Libraries, 2015)
Much recent attention has focused on bats as potentially exceptional reservoirs of pathogens. Bats are known to carry zoonotic viruses deadly to humans with no apparent signs of pathology, however the evolutionary and physiological processes that are behind this ability remain largely unknown. Despite this uncertainty, bats’ long lifespans, deep evolutionary history, sociality, and migratory behavior make them a fascinating system in which to study patterns of diversity in viruses, bacteria, and other infectious organisms. This thesis explores ecological and evolutionary processes that structure the diversity of infectious bacteria in bats. I focus on Bartonella, a genus of vector-borne intracellular bacteria, because of its high prevalence and genetic diversity within bats. I examined the structure of Bartonella species assemblages in Eidolon spp. fruit bats across Africa and Madagascar using newly developed molecular and statistical tools. The results from this examination indicate that fruit bats from distant geographic locations host similar communities of Bartonella; I attribute this to widespread dispersal and communal roosting behavior in Eidolon spp. bats. To understand how Bartonella diversity has evolved and is structured geographically, I assembled a global dataset of Bartonella genotypes from bats and their ectoparasites. Using this dataset, I analyzed the contributions of cospeciation and sympatry among host species to the diversity of Bartonella in bats. Continued development of this research could provide a model system for the study of ecological and evolutionary processes contributing to pathogen diversification and infection dynamics in natural systems.
Keywords: cophylogeny; molecular genetics; disease ecology; bartonella